2000
DOI: 10.1177/016327870002300203
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Response Rates to a Smoking Survey for U.S. Navy Enlisted Women

Abstract: This study examined the effectiveness of several persistent strategies to increase the response to a smoking survey among newly enlisted U.S. Navy women. The stepped approach, which included the use of incentives, repeated mailings, alternative survey administration modes, and reminders, was evaluated in terms of effects on response rates and response bias. Demographic and baseline smoking-related characteristics were compared for those responding on time to the initial mailed follow-up survey, reluctant respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Up to three attempts per participant were made to elicit a completed survey. The follow-up response rate was approximately 40%; this response rate, although low, is similar to those seen in other mailed military survey studies [1,31]. (As a specific point of comparison, the mailed portion of the most recent World Wide survey to remote Naval personnel had a 33.3% response rate, in contrast to higher group administration response rates [1]) The surveys were confidential rather than anonymous, because we were attempting to link individual self-reports at the two waves of the survey.…”
Section: Methodssupporting
confidence: 86%
“…Up to three attempts per participant were made to elicit a completed survey. The follow-up response rate was approximately 40%; this response rate, although low, is similar to those seen in other mailed military survey studies [1,31]. (As a specific point of comparison, the mailed portion of the most recent World Wide survey to remote Naval personnel had a 33.3% response rate, in contrast to higher group administration response rates [1]) The surveys were confidential rather than anonymous, because we were attempting to link individual self-reports at the two waves of the survey.…”
Section: Methodssupporting
confidence: 86%
“…While it has fallen out of favor among survey researchers, the continuum of resistance concept posits that later responders would be more similar to nonresponders than early responders. Previous research has either contradicted the continuum [42] or failed to find conclusive evidence for it [28,43]. The extensive data available on both responders and nonresponders from this data set allowed us to test the assumptions of this concept more thoroughly than has been possible in prior research, and the result of no differences found between mail responders and nonresponders seems to offer some support for a continuum of resistance.…”
Section: Demographic Differences and Mixed Modementioning
confidence: 70%
“…Numerous studies have examined non-response bias in substance use surveys, but have shown no clear patterns of results. Compared to respondents in some research, non-respondents reported higher use of alcohol (Goldberg et al, 2006;Heath et al, 2001;McCoy et al, 2009;Torvik et al, 2012;Wild et al, 2001;Zhao et al, 2009), cigarettes (Boström et al, 1993;Cunradi et al, 2005;Goldberg et al, 2006;Hill et al, 1997;Korkeila et al, 2001;McCoy et al, 2009;Smith and Nutbeam, 1990;Torvik et al, 2012;Woodruff et al, 2000) or cannabis (Zhao et al, 2009). In contrast, some studies showed no significant differences between non-respondents and respondents on alcohol use (Cunradi et al, 2005;Gmel, 2000;Korkeila et al, 2001;Kypri et al, 2004;Strote et al, 2002;Trinkoff and Storr, 1997;Ullman and Newcomb, 1998), tobacco use (Strote et al, 2002;Ullman and Newcomb, 1998) or cannabis use (Ullman and Newcomb, 1998) outcomes.…”
Section: Introductionmentioning
confidence: 98%